(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
With an increasing ageing population, the incidence of pressure sores and incontinence is becoming an increasing burden on the health sector and requires new forms of intervention. Three dimensional knitted spacer fabrics can afford a range of properties making them ideal for use against the skin in a variety of medical applications. Fabrics can be engineered with the appropriate choice of yarns to meet a range of product specifications with each layer having a different characteristic. Spacer fabrics are washable and thus reusable making them viable alternatives to disposable products in the medical sector, at a time when there is great emphasis on sustainability and the environmental impact of textile products. Focusing on medical applications requiring bulk liquid absorption, a range of three dimensional weft knitted spacer fabrics were produced and evaluated for desirable properties such as high absorbency and liquid retention using standard test methods. The surface of the fabric was engineered to afford rapid liquid transfer. The level of liquid spreading on the surface of the fabric could be measured using conventional test methods, however to understand how the liquid spreads at different points through the thickness of the fabric a new test method was designed. Results of testing showed good repeatability and use of the prototype test method offering scope for further development.